Highly Accurate Numerical Solutions of Elliptic Boundary Value Problems on General Regions (Journal of Computational Mathematics, 1986)
We prove that Lin Qun and Lu Tao's splitting extrapolation method and correction method can be effectively applied to raise the accuracy of the numerical solution of elliptic boundary value problems on general regions, i.e., to obtain approximate solutions with fourth- or fifth-order precision in the maximum norm.